長時間運転時における光刺激に対する反応時間の変化 - 早田, 有利; 小栗, 宏次; 柴田, 千里; 入部, 百合絵 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Recently, about half of traffic fatality are caused by human error. The incorrect recognition, judgment and operation while driving increases the risk of leading to traffic accident. Therefore, researchers attempt to evaluate the performance of recognition, judgment and operation by measuring reaction time while driving. Previous studies found that lowering of driver awakening level occurs delay in reaction time. However, it has not been verified how much time passed from starting to drive occurs delay of reaction time. The purpose of this study is to verify the difference in reaction time to the visual attention while long hour driving. Five subjects drove 15 lap round courses of one lap 3670m course simulating the city using a driving simulator in the experiment. We measured reaction time to LED turning on at intervals of 2-4 seconds by pushing a switch on the handle while driving. As a result, there was difference in features of reaction time to light stimulus while long hour driving.